TRANSLATION APPROACH OF ENGLISH METAPHORS INTO INDONESIAN (A CROSS CULTURAL UNDERSTANDING STUDY) - Ade Mulyanah (Pusbindiklat - LIPI, 2011)
This descriptive qualitative research aims at classifying important aspects related to sociolinguistics in rendering English metaphors into Indonesian. The study touches on several aspects dealing cross cultural understanding in translating metaphors taken from novel, TV serial, text bookin 2008. The cultural aspect in metaphors is related to important aspect of metaphors, namely, point of similarity, image, and figurative language. There are four types of metaphors in the paper: closed similes, open similes, live metaphors, and dead metaphors. The research reveals that: (1) Translation of closed similes can be rendered by applying literal translation meaning the focus of translation is on linguistics point of view. Translating direct metaphors (similes) is easier to transferthan indirect comparison (‘live’ and ‘dead’ metaphors). Transferring open similes needs the knowledge of the source and target language culture due to the absence of the point of similarity in the sentence. While, translating “dead” metaphors can be more understandable than ‘live’ metaphors by considering topic, image, and figurative language in both languages. (2) The paper is also trying to perform the difficulties in rendering English metaphors into Indonesian occur due to lack of standard Indonesian equivalent.